Force-induced repolarization of an active crawler. (19th March 2019) - Recho, Pierre; Putelat, Thibaut; Truskinovsky, Lev
Abstract: We develop a quantitative model of mechanical repolarization in a contraction-driven gel layer mimicking a crawling cell. We show that the force-velocity relations for such active crawlers exhibit multi-valuedness and hysteresis under both force and velocity control. The model predicts steady oscillations of cells attached to an elastic environment and offers a self-consistent mechanical explanation for all experimentally observed outcomes of cell collision tests.